Kesejahteraan psikologis dan mekanisme pertahanan pada anak dengan orang tua bercerai - Aulia, Putri Regina; Prabowo, Adhyatman (Cognicia, 2023)
Abstrak. This research was conducted to determine the relationship between psychological well-being and the use of defense mechanism's in young adults whose parents are divorced. This research uses a quantitative research design with a correlational approach. The research subjects were early adult children (18-25 years) with divorced parents, using the Accidental Sampling technique with 105 respondents. The instruments in this research are the psychological well-being Scale and the Defense Style Questionnaire. Data analysis uses Pearson correlation and Spearman rank. The results showed that psychological well-being and self-defense mechanism's (immature) were negatively significant with a value of p=0.005 and R=- 0.271. The higher a person's psychological well-being, the lower the use of defense mechanism's that are classified as immature. Kata Kunci: Child of divorce, defense mechanism, psychological well-being